Studi Pemanfaatan Bambu Berdasarkan Filososofi Tri Hita Karana Pada Era Millenial - Putu Ryan Widyastaguna; I Nengah Suka Widana; Ni Nyoman Parmithi; N. Putri Sumaryani (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2023)
Abstract. The aim of the research is to determine the behavioral tendencies of Balinese people in the millennial era regarding their understanding and behavior in using bamboo for life based on the Tri Hita Karana philosophy. This type of quantitative descriptive research, data acquisition using survey techniques, on purposive samples throughout Bali. Research data was analyzed using quantitative descriptive statistics. The results of the research show that in the palemahan field, the tradition of using bamboo materials is still very strong, namely 24.17% very often; often as much as 48.9%, and rarely as much as 21.1%. So as many as 94.1% of people still use bamboo. In the Pawongan sector, especially for medicine, there are still many people who do not know that bamboo material can be used as medicine. From the respondents' answers, 37.41% said they didn't know, or rarely used it. Meanwhile, in the field of parahyangan, the use of bamboo is still very large, namely 100%, meaning that the tradition of using bamboo is still very strong among the Balinese people.